Perceived benefits and receptivity to sport psychology consulting services of elite athletes in developing nations of the Oceania region - Neumann, D. L.; Piatkowski, T. M.; Moffitt, R. L.; Minahan, C. L. (International Journal of Sports Science & Coaching, 2024)
Sport psychology consulting services are commonly used by elite athletes in developed countries, but little is known about the athlete's perceptions of such services in developing countries. The present study examined the accessibility, receptivity, and perceived benefit of sport psychology services (via a sport psychology services questionnaire) through a cross-sectional survey of elite athletes (N = 32; Mage = 23.06 years, SD = 5.81) from 12 nations of the Oceania region who participated in the Gather, Adjust, Prepare, Sustain programme. These nations were Vanuatu, Fiji, Tuvalu, Tonga, Solomon Islands, Cook Islands, Norfolk Island, Niue, Nauru, Kiribati, Samoa, and Papua New Guinea. The results revealed that only a quarter of the athletes had ongoing access to sport psychology consulting services. Over half reported that they were receptive to sport psychology services and perceived that these types of services would be beneficial. The most desired services related to performance enhancement (e.g. performance under pressure). The athletes reported mixed levels of knowledge regarding mental skills, and most knowledge concerned the use of mental skills in competition. Specifically, most athletes rated their knowledge of mental skills at either the low (e.g. imagery) or high (e.g. goal setting, focus, and self-talk) range, and relatively fewer athletes rated their knowledge in the mid-range. The athletes demonstrated interest in learning more mental skills to enhance their performance. These findings indicate that a need exists for sport psychology service providers among athletes in the Oceania region. Existing non-local providers may also consider supplying services through digital modalities.